Combining Emotion Appraisal Dimensions and Individual Differences to Understand Emotion Effects on Gift Giving. (5th February 2016) - De Hooge, Ilona E.
Abstract: Multiple studies have revealed that emotion appraisal dimensions can predict the effects of emotions on decision making. For example, givers' intention to buy gifts depends on whether they feel positive or negative (valence) and on whether the feeling is caused by the givers themselves or by gift receivers (agency). However, there is little understanding of how the effects of such appraisal dimensions might depend on individual characteristics. The current research addresses this gap by studying the interaction effects of emotions and individual characteristics on gift giving. Study 1 demonstrates that emotion effects on gift‐giving behavior are explained by two things: the cause of those emotions (self or others, agency) and whether those emotions are positive or negative (valence). Moreover, four studies reveal that these effects depend on the givers' interpersonal orientation. For high interpersonally oriented givers, who care mostly about interpersonal relationships, emotion effects on gift giving depend on both valence and agency. In contrast, for low interpersonally oriented givers, who care mostly about their own gains, emotion effects on gift giving depend only on valence. Together, these findings suggest that although a focus on appraisal dimensions can be useful, individual characteristics should also be taken into account when trying to understand emotion effects on gift giving, in particular, and on decision making, in general. Copyright © 2016 John Wiley & Sons, Ltd.